ANALISIS PENGARUH POLA PENGAMBILAN DAN INJEKSI UNTUK MEMPERKECIL DAMPAK TERHADAP PENURUNAN MUKA AIR TANAH MENGGUNAKAN SIMULASI NUMERIK - MULIA , SIMSON
pendency on groundwater as the main source of fresh water for industry. Intense groundwater extraction may cause water table drawdown over the safe yield. This research is an analysis of rain water and surface water used to prevent excessive groundwater extraction. This effort is performed by processing rain water and river water to substituted groundwater use and injecting the surplus into the exploited bed. This research is conducted using a numerical simulation method and took a case study on PT. Excel Metal Industry, Village of Sukadanau, District of Cikarang Barat, Regency of Bekasi, and Province of Jawa Barat. The first step of numerical simulation method is to build a model based on geologic and hydrogeologic conditions. The next step is to calibrate the simulated water table with the natural water table. Well calibrated model is applied to predict the effect of groundwater extraction and groundwater injection toward the water table fluctuation. The simulated result of pumping with total discharge of 435 m3 per day until 2010 is a water table drawdown of 20 meters. An increase of pumping rate to 735 m3 per day will cause an excessive drawdown (32 meters). The addition of wells combined with a planned water source substitution and injection will result in a maximum drawdown of 25 meters on October 2008, 20 meters on October 2009 and 2010.